Pobreza y medio ambiente: una medición con micro-datos para el Norte Grande Argentino - González, Fernando Antonio Ignacio (2019)
This paper attempts to analyze the links between urban poverty and environment, with special emphasis for the case of the Norte Grande Argentino in the 2011-2016 period. For this purpose, the environmental conditions experienced by poor people and their situation in relation to the non-poor are analyzed, using indicators related to household sanitary conditions, housing location, and sources of energy used. In all cases with data provided by the Permanent Household Survey published by the National Institute of Statistics and Census. The results indicate that poor face a more deteriorated environment than the non-poor and that this situation worsens in the Norte Grande Argentino in relation to the rest of the country.